Revisión sistemática de la literatura sobre la micro filtración apical de los cementos selladores grossman, top seal, sealapex, AH-plus y MTA con técnica de obturación lateral entre el año 2015 al 2020 (2020)
Currently on the market we find various types of cements, some an epoxy resin base, others an MTA base, a zinc oxide base, among many other compounds, therefore the selection of the best sealing cement becomes complex, since all they have very good results and physico-chemical properties ideal for endodontic treatments; In this systematic review we found the studies carried out and published in the last 5 years (2015-2020), focusing the study on the most commercially found sealant cements and most used in general dental practice. This systematic review was carried out qualitatively and not quantitatively, because in the studies found, different measurement techniques and instruments were used, only the lowest apical microfiltration presentation and the greatest penetration into the dentinal tubules were referred to as the most efficient cement, in the information found in the publications. 5 sealant cements were compared, such as: Grossman, Top Seal, Sealapex, AH-Plus and MTA, filling with the lateral condensation technique, which evaluated the presence of apical microleakage in each study from lowest to highest, resulting in the lowest Apical microfiltration of the MTA sealant cement.